Impact of servicescape on customer loyalty in the fast food industry in asaba - Iyadi, Rollins C.; Egwuenu, Sylvester (International journal of economic perspectives, 2017)
This study examined the impact of servicescapes on Customer Loyalty in Nigeria fast food Industry, a study of the fast-food industry (Chrunchis, Macdons, Ultimate Taste, Mr. Bigs and Rodina) in Asaba, Delta State. This was done concerning the measures of servicescapes {Physical Architecture (PA), AmbientCondition (AC), Sign, Symbols and Artifacts (SSA), and Spatial Layout and Functionality (SLF). The sampling object used for this work comprises the customers of Chrunchis, Macdons, Ultimate Taste, Mr. bigs, and Rodina in Asaba, and their responses were collected with the aid of five (5) point Likert scale questionnaire. The study targeted a sample size of 100 respondents, and a total of 89 questionnaires administered were properly filled and returned. That means the response rate was 89%. The sample size used for the study was a total of eighty-nine (89) respondents. The questionnaire was coded with the aid of an excel spreadsheet, the respondent's profile was analyzed with manual simple percentage, the research questions were analyzed with the aid of descriptive statistics which comprised the minimum, maximum, mean, and standard deviation and correlation matrix and the hypotheses of the study were tested using the multiple regression statistical tools with the aid of SPSS version 23. The findings revealed that there is significant positive relationship between Physical Architecture (r= 0.370>0.05), Ambient Condition (r= 0.370>0.05), and Sign Symbols and Artifacts (r= 0.977>0.05), Spatial Layout and Functionality (r= 0.298>0.05) with Customer Loyalty (CL).